Prolactin Receptor Isoforms as the Basis of Tissue-Specific Action of Prolactin in the Norm and Pathology - Abramicheva, P. A.; Smirnova, Olga V. (Biochemistry-Moscow, 2019)
The review describes functional and structural features of different isoforms of prolactin receptor, mechanisms of signaling pathway activation, and molecular messengers involved in the transmission and termination of signal from the prolactin receptor isoforms. Changes in the ratio between prolactin receptor isoforms, key mediators of prolactin signal transduction and termination in various organs and tissues, are analyzed. Special attention is given to the role of molecular mediators and the ratio between the isoforms in normal physiological functions and pathologies. Approaches for therapeutic correction of prolactin signaling impairments are discussed.
CRIS-Team Scopus Importer:2023-04-20
Keywords: prolactin; prolactin receptor isoforms; prolactin receptor knockout; prolactin signaling; SOCS and PIAS proteins; STAT proteins